La cuestión agraria en La Laguna durante la Revolución - Plana, Manuel (El Colegio de México, A.C., 2000)
This work analyzes the impact of the 1910-1920 Mexican Revolution on land issues in the region of La Laguna. Drawing on evidence from local and national  sources,  the author claims that Villa's movement favored the settlement of small sharecroppers in the haciendas after their confiscation in 1914, and modified leasing procedures by introducing sharecropping contracts. Villa's different "commissions" managed to solve the region's social dissatisfaction and conditioned the policy of hacienda restitution established by Carranza's govemment in 1916. The  author concludes that  the social  upheaval  of 1911 and Villa's domination during 1914-1915 produced changes in the social and production structures of the cotton hacienda of La Laguna.